To explore access to respite care services through the acute care services from the perspectives of parents of autistic children - Cooke, Emma Louise (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2023)
Background: Research has consistently shown that parenting an autistic child can be challenging and stressful. Respite care offers a break for parents who experience such stress and also provides positive opportunities for the child to interact with their peers. In the absence of defined pathways to respite care in Ireland, parents of autistic children are accessing the acute services as a means to accessing respite care. To date, little is known about parental experiences of accessing respite care services, especially with respect to the complex decision- making involved and navigation of pathways. This study provides a comprehensive understanding of parent’s lived experience of accessing respite care for their autistic child through the acute care services. Method: A hermeneutic phenomenological approach underpinned the collection and analysis of data. Semi-structured interviews of 15 parents who had experience of accessing respite care through the acute care services for their autistic child took place during 2020 and 2021. Results: Analysis of the interview data, using Van Manen’s framework (2007, 2014) revealed five themes and 11 corresponding subthemes that reflected parents’ lived experiences. The five overarching themes are as follows: Parents’ experience of caring for an autistic child; Complex system of multiple interactions with services and health and social care professionals; Accessing acute care services for respite care: A last resort; Accessing respite care: An ongoing process across the lifespan; Acquired knowledge and information: Requirements for effective respite provision. Findings identified an overwhelming need for respite care but parents were faced with many barriers when accessing respite across their autistic’s child’s lifespan. Conclusion: This study provides a unique insight into the lived experience of accessing respite care through the acute care services from the perspective of parents of autistic children. Findings identified a number of implications for practice, policy, service delivery, education as well as social and cultural implications. In summary, this study highlights a critical need for effective implementation of integrated healthcare services for autistic children and adolescents whose numbers are rapidly growing.
APPROVED
Keywords: Respite Care; Autism; Integrated Care; Mental Health; Access